The Flavour of CSR in Indonesia: A comparative study of 3 Indonesian State-Owned Banks - Sapphira, Anya Sapphira (2011)
CSR has been recognized in Indonesia for the past decade, and it keeps developing. Together with other developing countries in Asia, Indonesia shows more attention on the issue of CSR and its implementation. A significant step related to CSR in Indonesia is when the government of Indonesia released the Social and Environmental Responsibility (TJSL) regulation in 2007. Although until now, the regulation has not been equipped with practical standard such as government regulation, on CSR definition and any other explanation toward this law, business sector already show their reaction. The fact shows that there are massive CSR activities done by corporation right after the government passed the law. This study aims to understand the Indonesian context of CSR and how domestic company, specifically the state-owned banks, react to the environment changes and how this regulation affecting their CSR agenda. Using the institutional theory by Oliver (1991) as the analysis framework, this study hopes to be able to answer the research questions and contribute to the general understanding of CSR in national context.